Does hotel employees' quality of work life mediate the effect of psychological capital on job outcomes? - Kim, Taegoo (Terry); Karatepe, Osman M.; Lee, Gyehee; Lee, Seungjae; Hur, Kyungsuk; Xijing, Cui (Emerald Group Publishing Ltd, 2017)
Purpose - This study aims to investigate quality of work life (QWL) as a partial mediator of the impact of psychological capital (PsyCap) on service recovery performance (SRP) and turnover intentions (TI). Design/methodology/approach - Data were obtained from 288 frontline employees in ten five-star hotels with a one-month time lag in three waves in Busan, Korea. Structural equation modeling was used to assess the direct and mediating effects. Findings - As expected, PsyCap heightens QWL and SRP, while it reduces propensity to leave the current organization. QWL partially mediates the association between PsyCap and the two critical outcomes. Practical Implications - Management of hotels should recognize the importance of PsyCap and assess candidates' PsyCap during selection process. Using the PsyCap questionnaire, organizations can select candidates who possess positive personal resources. In addition, hotels may consider the assessment of frontline employees' PsyCap to ascertain which employees can succeed in challenging situations. It is also important to create a healthy and happy environment where employees are willing to be more productive and contribute more to organizational performance. Originality/value - The extant hospitality research is devoid of empirical evidence about the outcomes of PsyCap and QWL such as SRP.
Keywords: Psychological capital; Quality of work life; Hotel employees; Turnover intentions; Service recovery performance